Culture and conformity A meta-analysis of studies using Asch's (1952b, 1956) line judgment task. [article]. - Bond, Rod
A meta-analysis of conformity studies using an Asch-type line judgment task (1952, 1956) was conducted to investigate whether the level of conformity has changed over time and whether it is related cross-culturally to individualism?collectivism. The literature search produced 133 studies drawn from 17 countries. An analysis of US studies found that conformity has declined since the 1950s. Results from 3 surveys were used to assess a country's individualism?collectivism, and for each survey the measures were found to be significantly related to conformity. Collectivist countries tended to show higher levels of conformity than individualist countries. Conformity research must attend more to cultural variables and to their role in the processes involved in social influence. -- (from the author)